Community work with migrant and refugee women : 'insiders' and 'outsiders' in research and practice - Thompson, Naomi; Nasimi, Rabia; Rova, Marina; Turner, Andy (Emerald points., 2022)
Marginalised migrant groups face significant barriers in accessing services and becoming integrated in their communities. Mainstream services are failing to engage many marginalised migrant and refugee women and to respond effectively to their needs, raising serious questions as to how community development might respond and facilitate positive spaces and reduce isolation. Community Work with Migrant and Refugee Women: 'Insiders' and 'Outsiders' in Research and Practice outlines the implications for policy, practice and meaningful research with migrant and refugee women drawing on a three-year case study of a community-based organisation working with marginalised Muslim women in London. Arguing for a bottom-up approach that centres on needs as well as assets, Community Work with Migrant and Refugee Women highlights the importance of cultural relevance of services, and a holistic approach to integration that acknowledges the full range of needs and experiences migrant and refugee women face. Co-written by academic researchers and practitioner-researchers, this volume contributes to both academic and policy debates where there is a need for more research and policy that understands the experiences of migrant and refugee women as well as which interventions are effective.